Development of Interactive E-Modules in Physical Education for Badminton Material for Seventh Grade Junior High School Students in Kendal Regency - Alif Mazida Salsabila; ipang setiawan (Journal of Physical Education and Sports, 2026)
This study was motivated by the use of teaching materials that are still dominated by conventional printed modules that are less interactive, less varied, and not yet integrated into a single digital platform that combines material, technical visualization, exercises, and evaluation. This study aims to produce interactive E-Modules that are suitable and effective for badminton material for seventh grade junior high school students. The method used is Research and Development (R&D) with the Borg and Gall model consisting of 10 steps. Data were collected through observation and questionnaires, then analyzed descriptively, quantitatively, and qualitatively. The results of validation by media experts, subject matter experts, and learning experts obtained an average of 92% (excellent category). The small-scale trial obtained 83% (very good), and the large-scale trial obtained 90% (very good). The effectiveness test showed a percentage of 87%, so the E-Module is categorized as effective. Thus, the interactive E-Module developed is feasible and effective for use in supporting learning in junior high schools.